Comparative analysis of the pathogenesis-related protein 10 gene family and their role during legume symbiosis - Takhi, Toufik Yahia; Berrabah, Fathi, Directeur de thèse; Gruber, Véronique, Directeur de thèse (Laghouat : Université Amar Telidji - Département de biologie, 2024)
Pathogenesis-related class 10 (PR10) proteins play various roles during plants’ growth and resistance to biotic and abiotic stress. However, little is known about their role in the context of legume-rhizobia symbiosis, particularly in nodules. This present study aims to bridge that gap by characterizing the various roles of PR10s in the nodules of Medicago truncatula (Medtr). Initially, phylogenetic analysis of PR10s revealed two distinct PR10 groups, PBI and PBII. The expression analysis performed on nodules of two Medtr mutants, symbiotic Cysteine-rich Kinase-Like (symCRK) and defective in nitrogen fixation 2 (dnf2), showed an upregulation of PR10s in symCRK and dnf2 mutant nodules compared to the WT, with PBI showing a higher expression than PBII. Collinearity analysis revealed three collinear PR10 gene pairs that all belong to PBI, suggesting that PR10s were possibly subjected to tandem gene duplication. The multiple sequence alignments of 500 nucleotides up-stream PR10 genes show a high conservation of 250 nucleotides in that site between PBI PR10 genes and a loss of this conservation in PBII PR10 genes. The conserved 250 up-stream nucleotides display a high density of putative binding sites for bZIP, NAC, and Myb transcription factors. Interestingly, molecular docking findings highlight that PBI PR10s bind phenolic compounds more efficiently than PBII. Moreover, multiple sequence alignments revealed that, unlike PBII PR10 proteins, PBI proteins have a high conservation of RNase motifs, which are important for the activation of programmed cell death during plant defenses. Finally, protein enrichment data revealed that PR10s can additionally accumulate in the different cellular compartments of nodules, including the cytoplasm, microsomes, and symbiosome. Altogether, our data show that PBI PR10s of M. truncatula are more conserved and highly functional during nodule defense responses compared to PBII PR10s. Thus, this study provides a valuable understanding of PR10s and their role during legume-rhizobia symbiosis.